2004
DOI: 10.1116/1.1767038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of resist-trimming processes by quasi in situ x-ray photoelectron spectroscopy

Abstract: We have used x-ray photoelectron spectroscopy (XPS) to investigate the resist-patterns’ transformations after exposure to resist trimming plasmas. The influence of the chemistry, the feed gas ratio, the bias power and the pressure have been studied for a Cl2/O2 and a HBr/O2 trim chemistry. An experimental procedure based on the chemical-topography analysis of resist patterns using XPS has been set up to determine the chemical composition and thickness of the reactive layers that are formed both on tops and sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In the present article, we have used mass spectrometry to confirm the hypothesis suggested in the previous article, 3 concerning the deposition of resist-etch-by-products on the resist sidewalls directly correlated with the low trim rates measured in Cl 2 /O 2 plasmas. Moreover, as XPS analyses are not relevant to explain the trim rate variation with the plasma parameters in HBr/ O 2 chemistries, mass spectrometry can be an interesting source of information to progress in the understanding of trim mechanisms using this chemistry.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the present article, we have used mass spectrometry to confirm the hypothesis suggested in the previous article, 3 concerning the deposition of resist-etch-by-products on the resist sidewalls directly correlated with the low trim rates measured in Cl 2 /O 2 plasmas. Moreover, as XPS analyses are not relevant to explain the trim rate variation with the plasma parameters in HBr/ O 2 chemistries, mass spectrometry can be an interesting source of information to progress in the understanding of trim mechanisms using this chemistry.…”
Section: Introductionsupporting
confidence: 82%
“…In a previous article, 3 we have shown that an increase of the oxygen concentration introduced in the plasma leads to an increase of the vertical and lateral etch rates, for both chemistries.…”
Section: Influence Of Oxygen Percentage Introduced In Reactormentioning
confidence: 84%
See 2 more Smart Citations
“…There are several possible known nonvolatile residues, which can be deposited, such as TiO x N y , SiO x , or CO x Cl y . 15,23,24 As mentioned earlier, these components are not soluble in H 2 O 2 . As N 2 gas flow increases, the formation of TiO x N y could be reduced due to the reaction of nitrogen with oxygen to form nitric oxide.…”
Section: B Effect Of N 2 Gas Flow On Etch Rates and Nonvolatile Resimentioning
confidence: 99%